Career Adabtability And Work Engagement In Gojek Driver - Feptiono Fitrah Ramadhan; sowanya ardi prahara (Universitas Pendidikan Ganesha, 2020)
The current research aims to examine the relationship between career adaptability and work engagement. The subjects in this study were 74 people who had the characteristics of a Gojek driver in Yogyakarta, who had worked for at least one year. How to take the subject using purposive sampling method. The data analysis technique used is the product moment correlation from Karl Pearson. Based on the results of data analysis obtained correlation coefficient (R) of 0.737 with p = 0,000 (p <0.05). These results show that there is a significant positive relationship between career adaptability with work engagement. This research increase work engagement by increasing and building an adabtability career, so that optimal performance can be created both from within and for the achievement of organizational or company goals.